Real-life effectiveness of FLOT in resectable gastric cancer: existing challenges - Francesco Serra; Federica Valerio; Paolo Pedrazzoli; Jacopo Viganò; Riccardo Caccialanza; Daniela Cicognini; Anna Pagani; Salvatore Corallo (Drugs in Context)
Background: Gastric cancer has a high mortality rate. Therapeutic management must be multidisciplinary to offer the patient the best, personalized strategy.